Metallic nutrients in enset (Ensete Ventricosum) corm and soil sample from some West Shoa Zone, Oromia Regional State, Ethiopia - Teressa Bedada; Alemayehu Abebaw (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
The aim of this study was to investigate the essential and non-essential metals concentration in corm of Ensete ventricosum and soil samples from some West Showa Zone. Ca and Mg were determined complecometric titration method, K and Na were analyzed using Flame Absorption Emission spectroscopy and the other metals with flame atomic absorption spectroscopy after appropriate quality control measures were undertaken to verify and maintain the quality of the data generated. The optimized wet digestion method for corm and soil analysis was found effective for all of the minerals and as it was evaluated through the recovery experiment, a good percentage recovery 95% (Fe concentration in corm) to 112% (Pb concentration in soil) was obtained for the minerals identified. The results of this study showed that the average the metallic nutrient concentrations of elements in the soil sample were ranged in order of decreasing in (mg.kg-1) 3521.11(K) >3497.85(Mg) > 3461.59(Fe) > 3294.93(Ca) >1096.89(Na) > (93.99(Mn) >16.74(Zn) > 3.77(Cu) > 0.26(Cd) but, the concentration of Pb was not detected  and the metallic nutrient concentrations of elements in the corm were ranged in order of decreasing in (mg.kg-1)  16425.13(Ca) >13813.33(K) > 1323.55(Mg) > 1131.11(Na)  > 76.78(Fe) > 16.16(Zn) >2.77(Cu) >1.94(Mn) but, Cd and Pb were not detected. The nutrient concentrations of the metals were also compared with recommended maximum permissible limits and some international reports; and found to be in a good agreement indicating no exposure risk of using the corm of Ensete ventricosum under the current situation. Statistical test of significance using ANOVA revealed that there were significant differences (P<0.05) between the values of metals in the corm and soil samples obtained from all the sampling sites except Zn concentration for corm and Ca concentration in soil) is not found.